Comparison of weld characteristics between longitudinal seam and circumferential butt weld joints of cylindrical components. (April 2015) - Velaga, Satish K.; Rajput, Gaurav; Murugan, S.; Ravisankar, A.; Venugopal, S.
Highlights: Longitudinal seam and circumferential butt joint of AISI 304 cylindrical components. Three-dimensional and sequentially coupled thermo-metallurgical-mechanical analysis. Heat source fitting analysis for prediction of weld molten pool sizes. Discussion of influence of L-Seam and C-Seam weld joints on the residual stresses. Comparison of numerical simulation results with the experimental measurements. Abstract: The control of weld induced residual stresses and distortions are very important in longitudinal seam (L-Seam) and circumferential (C-Seam) butt joints of cylindrical components. In this study, a three-dimensional, sequentially coupled thermo-metallurgical-mechanical analysis was performed for L-Seam and C-Seam butt weld joints of AISI 304 cylindrical components to evaluate weld characteristics during gas tungsten arc welding (GTAW) process. Initially, weld experiments were carried out to obtain the heat input and the macrographs which were further validated with the predicted weld molten pool sizes during heat source fitting (HSF) analysis. The Goldak's double ellipsoid heat source function obtained in HSF analysis was employed in the thermal and mechanical analysis. The results reveal that there are significant differences in residual stress distributions between L-Seam and C-Seam butt joints. Full scale shop floor welding experiments were performed to verify the effectiveness of the proposed numerical models and these are in good agreement with the experimental measurements.